Endothelium-independent vasodilator effects of nobiletin in rat aorta - Hisako Kaneda; Rieko Otomo; Noriyasu Sasaki; Toshinori Omi; Tsuyhoshi Sato; Takeharu Kaneda (Elsevier, 2019)
Nobiletin is a one of the polymethoxyflavones contained in the peel of citrus fruits, such as Citrus depressa. In this study, the effect of nobiletin-induced relaxation on phenylephrine (PE)-induced contraction of endothelium-denuded rat aorta was investigated. Nobiletin inhibited PE- or KCl-induced contractions in a concentration-dependent manner in endothelium-intact and -denuded aortas. However, this relaxation was stronger in PE-induced contractions than in KCl-induced contractions; moreover, the nobiletin-induced relaxation was significantly increased on PE-induced contraction in endothelium-intact aorta. ODQ significantly inhibited the nobiletin-induced relaxation in endothelium-denuded aorta; however, SQ22536 did not affect the relaxation. In addition, IBMX synergistically enhanced the nobiletin-induced relaxation. Nobiletin increased cGMP levels in aorta. Also, IBMX significantly increased cGMP content in aorta, and ODQ significantly reduced cGMP levels. Nobiletin-induced relaxation was significantly inhibited by the Ca2+-activated K+ (BK) channel inhibitor iberiotoxin (IbTX) and the ATP-sensitive K+ (KATP) channel inhibitor glybenclamide. Sodium nitroprusside-induced relaxation was suppressed by IbTX, but not by glybenclamide. These results suggest that nobiletin inhibits PE-induced contractions of endothelium-denuded rat aorta by increasing cGMP levels via GC activation. Moreover, the present findings indicate the possibility that nobiletin opened BK channels by a cGMP-related signal, but KATP channels were opened by a cGMP-nonrelated signal in rat aorta. Keywords: Nobiletin, Relaxation, Rat aorta, cGMP, K+ channel